A Regional ADHD Center-Based Network Project for the Diagnosis and Treatment of Children and Adolescents With ADHD. Issue 12 (October 2018) - Bonati, Maurizio; Reale, Laura; Zanetti, Michele; Cartabia, Massimo; Fortinguerra, Filomena; Capovilla, Giuseppe; Chiappedi, Matteo; Costantino, Antonella; Effedri, Paola; Luoni, Chiara; Martinelli, Ottaviano; Molteni, Massimo; et al.
Objective: We aimed to define the sociodemographic, clinical, and prescription profiles of the participants enrolled in the Italian Lombardy ADHD Register.Method: Data on patients evaluated by the 18 regional ADHD reference centers in the 2012 to 2013 period were analyzed.Results: Seven hundred fifty-three of 1, 150 (65%) suspected patients received a diagnosis of ADHD. In 24% of cases, there was a family history of ADHD. Four hundred eighty-three (64%) patients had at least one psychopathological disorder, the more common of which were learning disorders (35%). Eighty-four percent of patients received a prescription for psychoeducational interventions, 2% received only pharmacological treatment, and 14% a combination of both. Compared with patients treated with psychoeducational intervention alone, patients with drug prescriptions more commonly presented values of Clinical Global Impressions - Severity scale (CGI-S) of 5 or higher ( p < .0001).Conclusion: A continuous and systematic monitoring of patterns of care is essential in promoting significant improvements in clinical practice and ensuring an efficient and homogeneous quality of care.